Deterministic Analysis of Wind Loads Effects on High-Rise Buildings (Journal of Engineering, 2015)
This paper studies the effect of mean wind velocity on tall building. Wind velocity, wind profile and wind pressure have been considered as a deterministic phenomenon. Wind velocity has been modelled as a half-sinusoidal wave. Three exposures have been studied B, C, and D. Wind pressure was evaluated by equation that joined wind pressure with mean wind velocity, air density, and drag coefficient.Variations of dynamic load factor for building tip displacement and building base shear were studied for different building heights, different mode shapes, different terrain exposures, and different aspect ratios of building plan. SAP software, has been used in modelling and dynamic analysis for all case studies.Results For different building heights considered maximum dynamic load factor (DLF) occurs in height range from 100-150m because fundamental building frequency is so close as to dominate wind frequency. Effects of higher modes become insignificant for height greater than 175m. Effect of three different terrain exposures B, C, and D on DLF for tips displacement and building base shear have been insignificant effect on response of tip displacement and building base shear. . Finally, effect of aspect ratio  for different building heights with dynamic load factor (DLF) for tips displacement and for building base shear have  approaching 2, fundamental building frequency is so closed to dominate wind frequency.